Incremental validity of the PID‐5 in relation to the five factor model and traditional polythetic personality criteria of the DSM‐5. Issue 2 (27th September 2016) - Fowler, J. Christopher; Patriquin, Michelle A.; Madan, Alok; Allen, Jon G.; Frueh, B. Christopher; Oldham, John M.
Abstract: Background: This study assessed the incremental validity of the Personality Inventory for DSM‐5 (PID‐5) beyond the impact of demographic, burden of illness, five‐factor model of personality, and DSM‐5 personality disorder criteria with respect to associations with admission psychiatric symptoms and functional disability. Methods: Psychiatric inpatients ( N = 927) were administered the Big Five Inventory, PID‐5, and personality disorder criteria counts. Prior treatment utilization, as well as baseline depression, anxiety, emotion regulation, and functional disability were administered within two days of the personality measures. Hierarchical regression models were used to explore the association of personality functioning with symptom functioning, emotion regulation and disability. Results: Neuroticism was associated with all symptom measures, providing further support for its relevance in clinical populations. Personality trait domains (negative affect, detachment, and psychoticism) from the PID‐5 demonstrated incremental validity in predicting baseline symptom and disability functioning over and above demographic, burden of illness, and psychiatric comorbidity and five‐factor model (FFM) personality traits. Conclusions: Dimensional measures of personality functioning were consistently associated with baseline symptom functioning, supporting the relevance of personality functioning as it relates to psychiatric symptoms. The PID‐5 uniquely contributed to the prediction of baseline symptom functioning, thus providing incremental validity over gold‐standard personality trait measures.